THE RELATIONSHIP OF CAUSING FACTORS WITH THE EVENT CERVICAL CANCER IN WOMEN - Signora, Khalisa Aisyah; Susanti, Nofi; Harsana, Amanda Putri; Sinantin, Ipak (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Cervical cancer is cancer that starts in the cervix. The cervix is the lowest part and end of the uterus or uterus. The cervix connects the uterus and the vaginal canal, and cervical cancer is caused by infection with the human papillomavirus (HPV). Objective: To describe the association between the incidence and causative factors of cervical cancer in women. Methodology: Methodological literature review. Results: The most major risk factors for cervical cancer are hormonal contraception and age. There are also other characteristic social factors, such as low education level, economic status, smoking, cleanliness, physical activity, place of residence, and family history, and most of these factors are risk factors that can be modified to take preventive measures.